2021
DOI: 10.3389/fnhum.2021.717810
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neural Dynamics of Interpersonal Synchrony Between Performing Musicians: A Wireless EEG Hyperscanning Study

Abstract: Interpersonal synchrony refers to the temporal coordination of actions between individuals and is a common feature of social behaviors, from team sport to ensemble music performance. Interpersonal synchrony of many rhythmic (periodic) behaviors displays dynamics of coupled biological oscillators. The current study addresses oscillatory dynamics on the levels of brain and behavior between music duet partners performing at spontaneous (uncued) rates. Wireless EEG was measured from N = 20 pairs of pianists as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 89 publications
1
10
0
Order By: Relevance
“…However, laboratory tasks may not capture the real-world complexity of therapy. In contrast, studies closer to real-world settings (i.e., “macro”) can explore broader dynamics, like weather therapist-patient brain-to-brain synchrony is increased when they create novel dyadic-level knowledge, similar to musicians playing together (Zamm et al, 2021). From our perspective, in the case of psychotherapy research, solely focusing on micro- or macro-cognitive processes might not allow us to properly understand the nature of expertise in therapists and the mechanisms of therapeutic change.…”
Section: Mobile Brain/body Imaging (Mobi): a Technico-methodological ...mentioning
confidence: 99%
“…However, laboratory tasks may not capture the real-world complexity of therapy. In contrast, studies closer to real-world settings (i.e., “macro”) can explore broader dynamics, like weather therapist-patient brain-to-brain synchrony is increased when they create novel dyadic-level knowledge, similar to musicians playing together (Zamm et al, 2021). From our perspective, in the case of psychotherapy research, solely focusing on micro- or macro-cognitive processes might not allow us to properly understand the nature of expertise in therapists and the mechanisms of therapeutic change.…”
Section: Mobile Brain/body Imaging (Mobi): a Technico-methodological ...mentioning
confidence: 99%
“…Additionally, these complex hyper-brain networks have also been investigated between a quartet of guitarists and four audience members, thus capturing brain dynamics of musical communication at multiple levels simultaneously (Müller & Lindenberger, 2023). Methodologically deviating from phase-based approaches, another study with wireless EEG hyperscanning of piano duets focused on amplitude-based analysis of INS by computing the power spectral density and EEG amplitude envelopes (Zamm, Palmer, et al, 2021). This study showed that neural oscillations were period-coupled between duet pianists, corroborating phase-based research.…”
Section: Multi-brain Approachmentioning
confidence: 99%
“…Behavioral studies have shown that two people can jointly entrain to a beat, and that being paired with a musician increases a non-musician’s ability to maintain a steady beat via tapping ( Schultz and Palmer, 2019 ). During joint music-making, humans temporally and affectively entrain to one another (see Phillips-Silver and Keller, 2012 for a review), resulting in synchronous brain activity ( Zamm et al, 2021 ). Using EEG paradigms, between-brain oscillatory couplings both before and during dyadic guitar playing have been linked to interpersonally coordinated actions ( Lindenberger et al, 2009 ; Sänger et al, 2012 ).…”
Section: How Has Real-world Musical Communication Been Studied and Wh...mentioning
confidence: 99%